Faktor – Faktor Fundamental Dan Beban Pajak Tangguhan Dalam Memengaruhi Manajemen Laba - Arry Eksandy; Riski Ulan Sari (Universitas Serang Raya, 2023)
The purpose of this study is to determine the influence of the company's fundamental factors, namely profitability and company size, as well as the burden of deferred taxes on earning management The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2021 a total of 154 companies. The sampling technique uses purposive sampling technique. The analysis method used is panel data regression. The results showed that the profitability variable had a significant negative effect on earning management, the deferred tax expense variable had a significant positive effect on earning management, while the company size variable had no effect on earning management.